Digital Humanities: A Transformative Approach to Teaching English Grammar in Remote Areas - Harshal Harish Potdar, Alpana Akolkar (Journal of Informatics Education and Research, 2024)
In today's world, English is a universal language of communication that fosters connections across national boundaries, industry boundaries, and cultural divisions. Its importance has grown significantly in several areas of modern life as a result of a confluence of historical, economic, and technical factors. In domains such as commerce, research, diplomacy, and higher education, English is the most extensively utilized language for global communication. English is the preferred language of instruction in a large number of prestigious universities and academic institutes worldwide. English has taken the lead in digital communication with the growth of the internet and social media. English is the standard language for internet usage, enabling cross-border connectivity in everything from social media and online content to email and e-commerce. Teaching English in rural places is not just about improving language skills; it's also about providing opportunities for social inclusion, educational access, economic empowerment, and global connectivity. In order to enable people living in remote places to prosper in a world that is becoming more interconnected, legislators, educators, and community leaders must see the value of teaching English and make investments in language education programs. The incorporation of Digital Humanities tools is a possible option for remaking English grammar training in rural areas where access to high-quality education is limited. In order to solve the educational obstacles faced by rural communities, this article investigates the transformative potential of Digital Humanities. It explores the ways in which digital tools might be used to create dynamic, interesting, and easily accessible grammar classes through an extensive analysis of case studies and literature. Through the provision of creative materials to educators and the utilization of technology to overcome geographic barriers, Digital Humanities not only improves the quality of instruction but also helps students who live in remote locations become more fluent in language. The significance of using digital advances to guarantee fair access to excellent English language instruction is emphasized in this abstract, which will ultimately help distant communities grow and become more empowered.